Pavel Kukolnik and Vladimir Nazimov - Лавринец, Павел (Literatūra, 2017)
A dozen verse texts by the Vilnius censor and the figure of the Vilna Archaeological Commission Pavel Kukolnik (1795–1884), written in 1859–1871, are dedicated to Vladimir Nazimov (1802–1874), the Governor-General of Vilna during 1855–1863, as well as his wife, daughters, pupil and two governesses. It was such an unusually generous case of dedications. To explain this, the testimonies of contemporaries and periodical press materials are used to analyze Nazimov’s activities and his relationship with the local society, Kukolnik’s relationship with Nazimov and his family and Kukolnik’s relationship with the local cultural environment. Kukolnik and Nazimov jointly participated in many official events; Kukolnik also met with Nazimov in private, since the Governor-General was open-minded, and his house was a hospitable place. However, the dedication to Nazimov and his family is motivated not only by the personal qualities of the Governor-General and by the warm attitude of his home environment toward Kukolnik; Nazimov’s activities in Vilna were oriented toward a compromise and cooperation with the Lithuanian society of that time. On the other hand, Kukolnik lived in Vilna since 1825, and in the 1850s, he became friends with a circle of local Polish writers and scholars (Adam Honory Kirkor, Antoni Edward Odyniec, Władysław Syrokomla and others). In his own words, Vilna became a part of him. Therefore, he evidently identified himself with the local cultural environment, shared its sympathies for Nazimov and associated certain hopes with him. The carried-out research allows to draw a conclusion that Kukolnik’s poetic dedications reflected the similarity of the Governor-General’s and the poet’s attitude toward interaction and cooperation with the environment of a different language, a different faith, a different culture, and it expressed the moods of the Vilna society of the late 1850s and early 1860s. PAVELAS KUKOLNIKAS IR VLADIMIRAS NAZIMOVAS Dešimtys Vilniaus cenzoriaus ir Vilniaus archeologijos komisijos veikėjo Pavelo Kukolniko (1795–1884) 1859–1871 m. parašytų eiliuotų tekstų buvo dedikuoti Vilniaus generalgubernatoriui Vladimirui Nazimovui (1802–1874), jo žmonai, dukroms, auklėtinei ir dviem guvernantėms 1855–1863 metais. Tokio nepaprastai gausaus dedikacijų korpuso paaiškinimui analizuojami Nazimovo veikla ir vietinės visuomenės santykiai su juo, Kukolniko santykiai su Nazimovu ir jo šeima, Kukolniko ir vietinės kultūrinės aplinkos tarpusavio santykiai remiantis amžininkų liudijimais ir periodinės spaudos medžiaga. Kukolnikas ir Nazimovas kartu dalyvaudavo oficialiuose renginiuose; Kukolnikas taip pat susitikdavo su Nazimovu privačioje aplinkoje, nes generalgubernatorius pasižymėjo atvirumu, o jo namai – svetingumu. Tačiau dedikacijos Nazimovui ir jo artimiesiems motyvuotos ne tik generalgubernatoriaus asmenybės savybėmis bei jo naminės aplinkos šiltais santykiais su Kukolniku. Nazimovo veikla Vilniuje buvo orientuota į kompromisą ir bendradarbiavimą su tuometinės Lietuvos bendruomene. Kita vertus, Kukolnikas gyveno Vilniuje nuo 1825 m. ir 6-ajame dešimtmetyje suartėjo su vietiniu lenkų literatų ir mokslininkų aplinka (Adomas Honorijus Kirkoras, Antanas Eduardas Odinecas, Vladislovas Sirokomlė ir kt.). Jo paties žodžiais, jis susigyveno su Vilniumi. Todėl jis akivaizdžiai tapatino save su vietine kultūrine aplinka, jautė tą patį palankumą Nazimovui bei siejo su juo tam tikras viltis. Atliktas tyrimas leidžia daryti išvadą, kad Kukolniko eiliuotos dedikacijos atspindėjo generalgubernatoriaus ir poeto sąveikos su kitos kultūros aplinka nuostatų panašumą ir išreiškė 6-ojo dešimtmečio pabaigos ir 7-ojo dešimtmečio pradžios Vilniaus visuomenės nuotaikas.